MicroRNAs in platelet biogenesis and function - Dangwal, Seema; Thum, Thomas (Thrombosis and Haemostasis, 2012)
Platelets are important to maintain primary haemostasis and play a key role in pathology of thrombotic and occlusive vascular disorders such as acute coronary syndrome or stroke. Despite of lacking a nucleus and genomic DNA, platelets possess diverse types of RNAs, ranging from protein coding messenger RNAs to small non-coding RNAs inherited from their parent megakaryocytes. Indeed, platelets are capable of using their own translational machinery to synthesise proteins upon their activation suggesting the possibility of post-transcriptional gene regulation in platelets. MicroRNAs (miRNAs) are highly conserved, tiny non-coding RNAs exhibiting a fine-tune control of protein expression by complementary sequence recognition, binding and translational repression of protein coding mRNA transcripts. Multiple functional aspects of miRNAs as well as their expression in platelets or megakaryocytes underscore a role in platelet biology. Changes in miRNA expression patterns have been noted during platelet genesis and activation. In the present review we highlight recently identified megakaryocytic/platelet miRNAs and discuss their role in platelet biogenesis and functions essential to maintain haemostasis in the body.
Keywords: Platelet reactivity; megakaryocytopoiesis; platelet miRNA; P2Y12